An improvement of LUC2 cryptosystem algorithm using doubling with remainder - Othman, Mohamed; Abulkhirat, Esam M.; Md. Said, Mohamad Rushdan; Johari, Rozita; Md Ali, Zulkarnain (2006)
The major factor that influences the performance of the LUC public-key cryptosystem is the computation of Ve and Vd, a public and private key, respectively. Its involve a huge steps of computations for large values of e and d. We concentrated our discussion on how to utilize and manipulate the doubling step technique for an efficient LUC2 computation. Therefore, we proposed the so-called Doubling with Remainder technique. It shows a better performance in LUC2 computations and also a great reductions of time consume for computations. The experimental results for sequential, doubling steps and doubling with remainder are also included.